Akurasi dalam Identifikasi Penyakit Sapi Pesisir Menggunakan Metode Forward Chaining - Hafiz Mursalan; Sumijan (Jurnal Informasi dan Teknologi, 2021)
Coastal cattle are livestock that have economic value, such as selling beef and cattle breeds. Cow disease can cause the quality of its sales to decrease. This study aims to help cattle breeders to determine the type of cow disease, from the symptoms that exist in these cows. So that the prevention of the risk of cow disease can be avoided. All data used are sourced from experts. In determining the type of disease in cows, the Forward Chaining method is used. The fact-finding technique is then put into the predetermined rules to get a conclusion. Making a website based expert system makes it easy for breeders to access it online. The accuracy of the system has been tested by related parties so as to produce fast and efficient information. From research, it can help breeders in diagnosing the symptoms experienced by cows and the test results can detect the type of disease accurately.